2018
DOI: 10.1136/bmjgast-2018-000239
|View full text |Cite
|
Sign up to set email alerts
|

Interference with the lower gut–liver axis induces remission of primary sclerosing cholangitis in a patient with ulcerative colitis

Abstract: The gut–liver axis describes the complex interactions between gut microbiota, the small and large bowel, the immune system and the liver. Current evidence associates abnormalities within the gut–liver axis with liver disease such as primary sclerosing cholangitis (PSC). PSC is believed to be an immune-mediated disease though the exact mechanism of its pathogenesis remains unknown. Here, we report a case of a 66 -year-old woman with treatment-resistant ulcerative colitis and PSC which continued to be active fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…[95][96][97] Still unresolved is why immunosuppressive therapy and colectomy do not appear to alter the disease course, perhaps indicating that some mechanisms are involved in the initiation of PSC but have little influence on disease progression. [98][99][100][101]…”
Section: Etiology Of Pscmentioning
confidence: 99%
See 1 more Smart Citation
“…[95][96][97] Still unresolved is why immunosuppressive therapy and colectomy do not appear to alter the disease course, perhaps indicating that some mechanisms are involved in the initiation of PSC but have little influence on disease progression. [98][99][100][101]…”
Section: Etiology Of Pscmentioning
confidence: 99%
“…Strictures of large bile ducts, reduced bile flow, increased biliary pressure, and alterations in bile composition associated with cholestasis may further drive disease progression 95–97. Still unresolved is why immunosuppressive therapy and colectomy do not appear to alter the disease course, perhaps indicating that some mechanisms are involved in the initiation of PSC but have little influence on disease progression 98–101…”
Section: Etiology Of Pscmentioning
confidence: 99%
“…[12][13][14]25,27 However, there is no evidence to support the theory that the inflammatory activity is associated with fast progression of PSC before liver transplantation. It has been hypothesized that the impact of the gut on the liver in PSC may be caused by pathogenic antigens or micro-organisms from other parts of the GI tract than the colon 28 or more likely to be affected by immunogenetics.…”
Section: Discussionmentioning
confidence: 99%
“…However, hepatic inflammation can be caused independently from gut inflammation. Indeed, PSC can develop many years after proctocolectomy in the absence of gut inflammation 66 . In this case, several studies have suggested the role of gut-homing lymphocytes.…”
Section: Introductionmentioning
confidence: 99%